How Much PEEP Does High Flow Deliver via Tracheostomy? A Literature Review and Benchtop Experiment. (13th January 2021) - Thomas, Martin; Joshi, Riddhi; Cave, Grant
Abstract : Background . High flow tracheostomy (HFT) is a commonly used weaning and humidification strategy for tracheostomised patients, but little is known as to how much PEEP or mechanical benefit it offers. Patient anatomy and device characteristics differentiate it from high flow nasal cannula and the physiological effects observed. Objectives . (1) To review the available literature on the effects of HFT on airway pressure and indices of gas exchange. (2) To quantify PEEP generated by a HFT  circuit. Methods . A randomised benchtop experiment was conducted, with a size 8 uncuffed Portex tracheostomy connected to an Optiflow™ with Airvo 2™ humidifier system. The tracheostomy tube was partially immersed in water to give rise to a column of water within the inner surface of the tube. An air fluid interface was generated with flows of 40 L/min, 50 L/min, and 60 L/min. The amount of potential PEEP (pPEEP) generated was determined by the distance the water column was pushed downward by the flow delivered. Findings . Overall 40 L/min, 50 L/min, and 60 L/min provided pPEEP of approximately 0.3 cmH2 O, 0.5 cmH2 O, and 0.9 cmH2 O, respectively. There was a statistically significant change in pPEEP with change in flows from 40–60 L/min with an average change in pPEEP of 0.25–0.35 cmH2 O per 10 L/min flow (p value <0.01). Interpretation . HFT  can generate measurable and variable PEEP despite the open system used. The pPEEP generated with HFT is minimal despite statistically significant change with increasing flows. This pPEEP is unlikely to provide mechanical benefit in weaning patients off ventilatory support.